(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the effectiveness of integrating EdTech elements into the educational process, specifically within a research-oriented discipline such as "Academic Writing" in a foreign language. The primary research question is formulated as follows: "What is the impact of gamification elements on the mastery of learning material and student motivation?" The authors analyze specific examples of educational technology implementation, which were piloted between 2023 and 2025 with fourth-year university students. The research methodology involved both qualitative and quantitative data collection methods,including surveys, observations, and focus groups conducted with students who had completed this discipline. The paper presents the results of integrating EdTech into the educational process during academic writing classes. The data obtained allow—with certain caveats—for the conclusion that this practice is both expedient and effective when applied in the classroom setting